المؤامرات و الاغتيالات السياسية في الدولة العباسية (232-477ه/847-1055 ) - جديد خيرة; د/ قاوي محمد (جامعة عمار ثليجي الاغواط, 2024)
ملخص المذكرة تناولنا في هذا البحث المؤامرات و الاغتيالات السياسية في الدولة العباسية في الفترة الممتدة ما بين (232-447ه/847-1055م) و الذي حاولنا من خلاله التطرق لأهم مظاهر الإحتقان السياسي و الصراع على الحكم و السلطة الذي تخلل الخلافة العباسية ، بدراسة أحد أهم جوانبه و هو المؤامرات و الإغتيالات . و هذا بالتطرق إلى تعريف بمصطلحي الاغتيالات و المؤامرات ، ثم دراسة الأوضاع السياسية التي تزامنت معهما،و عرض أهم المؤامرات و الاغتيالات التي عرفتها الدولة العباسية ، أثناء الفترة المدروسة ، و هذا بتعريف بشخصياتها ، و التطرق إلى أسبابها و دوافعها و طرق تنفيذها و البحث عن الغاية منها . الكلمات المفتاحية: المؤامرات السياسية، الاغتيالات السياسية ، الخلفاء ، الوزراء ، الأتراك ، البويهيين. In this research, we discussed the political conspiracies and assassinations in the Abbasid state during the period extending between (232-447 AH / 847-1055 AD). Through which we tried to address the most important manifestations of political . tension and the struggle for rule and power that permeated the Abbasid Caliphate, by studying one of its most important aspects, which is conspiracies and assassinations. This is by addressing the definition of the terms assassinations and conspiracies, then studying the political conditions that coincided with them, and presenting the most important conspiracies and assassinations that the Abbasid state knew, during the period studied, and this is by defining their personalities, and addressing their causes and motives and methods of implementation and searching for Its purpose. Keywords: political conspiracies, political assassinations, caliphs, ministers, Turks, Al-Buyhiyen